Pembelajaran kreatif menulis resensi buku bacaan anak - Pamuji, Slamet (JURNAL PENDIDIKAN DAN SAINS, 2024)
Education can be prepared carefully because it is a symbol of success in life. In fact, education requires interesting implementation and learning. Teachers are one of the implementers of teaching in schools, as a benchmark for success. With competent teachers and long experience in learning at school, the school will progress. This type of research uses descriptive analytics where researchers not only explain certain phenomena, but researchers participate in analyzing phenomena that occur in accordance with what occurs in the field. Learning resources are not only from textbooks, but can be obtained from books in the library. The use of library books can increase student motivation and improve writing by looking at the results of the sentence descriptions they write on student worksheets. In addition, students will be more active and enthusiastic in participating in learning as well as being able to creatively arrange words to fill in student worksheets.